Knowledge Mapping of Government Trust and Social Media Research: A Visual Analysis Using CiteSpace. Issue 2 (3rd April 2021) - Tong, Peishan; Song, Zhiping
ABSTRACT: The interaction between social media and government trust has been one of the most critical and dynamic research areas in the field of governance in recent years. In this paper, a scientometric analysis of 668 academic publications published from 2000 to 2018 related to social media and government trust is presented to characterise the intellectual landscape by identifying and visualising the evolution of the collaboration network, the co-citation network, and the emerging trends. The results show that the number of publications in this field has increased rapidly, and it has become an increasingly more popular interdisciplinary research subject. The most productive authors and institutions in this subject area are in the USA, China, Australia, and European countries. In this paper, we identify the most pressing topics of social media and government trust research as represented in the existing literature, which include the relationship between the Internet and governance, the impact of social media on government trust, and the contribution of social media to government trust and mitigation responses. The paper presents an in-depth analysis of social media and government trust research to better understand governance and the directions in this field that have emerged over the past 19 years.